2005
DOI: 10.1159/000084871
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Resistin Immunoreactivity Is Reduced b y Obesity in the Mouse: Co-Localization with α-Melanostimulating Hormone

Abstract: Resistin is a new adipokine expressed in mouse, rat and human adipose tissue. Resistin may be an important link between obesity and insulin resistance, though this controversial view is complicated by the discovery of multiple sites of resistin expression, including human macrophages, placenta and pancreas. In previous studies we demonstrated that the mouse hypothalamo-pituitary system was also a site of resistin production. Pituitary resistin is developmentally regulated, reduced in the ob/ob mouse and severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 89 publications
(66 reference statements)
7
28
0
1
Order By: Relevance
“…The only hypothalamic or forebrain region to show resistininduced Fos protein expression was the arcuate nuclei. These results are in concordance with previous works showing that resistin expression is co-localized with alphamelanostimulating hormone (a-MSH) in the arcuate nucleus (11). Even though Wilkinson et al observed that hypothalamic resistin mRNA remained unaffected by fasting, there was a marked reduction in resistin positive fibres from ob/ob mice and in underweight mice (11).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The only hypothalamic or forebrain region to show resistininduced Fos protein expression was the arcuate nuclei. These results are in concordance with previous works showing that resistin expression is co-localized with alphamelanostimulating hormone (a-MSH) in the arcuate nucleus (11). Even though Wilkinson et al observed that hypothalamic resistin mRNA remained unaffected by fasting, there was a marked reduction in resistin positive fibres from ob/ob mice and in underweight mice (11).…”
Section: Discussionsupporting
confidence: 92%
“…However resistin mRNA expression was found in the arcuate nucleus (11) and it remains unknown whether resistin is centrally active or whether it interacts with the hypothalamic circuits that regulate energy balance. The aim of the present study is therefore to seek evidence that resistin is a centrally active peptide participating in the control of energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin clamp was performed at 10 -12 weeks of age. Resistin is expressed in the arcuate nucleus and periventricular regions of the dorsal hypothalamus (Wilkinson et al, 2005); hence, clamp studies were also done in C57BL/6J retnϪ/Ϫ mice to ascertain the contribution of locally expressed resistin on glucose metabolism.…”
Section: Methodsmentioning
confidence: 99%
“…Because resistin is present in the CSF (Kos et al, 2007) and is expressed locally in the hypothalamus (Wilkinson et al, 2005), it is possible the change in insulin sensitivity involves hormonal as well as paracrine mechanisms. Thus, we determined whether centrally administered resistin was still capable of regulating glucose fluxes in the absence of endogenous resistin expression.…”
Section: Central Resistin Impairs Insulin Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation